Pendidikan Bahasa Arab Dengan Menerapkan Metode At-Thoriqoh Al-Istinqo’iyyah Pada Siswa Madrasah Ibtidaiyyah Tarbiyatunnasyiin Jombang - Salsabila, Salsabila; Rahardjo, Resdianto Permana; Naseha, Siti Durotun (Himpunan Mahasiswa Program Studi (HMPS) Pendidikan Bahasa Arab Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Negeri (IAIN) Jember, 2024)
This research is an experimental research, namely the researcher acts as a direct teacher in the learning process. This study aims to determine the effectiveness of using the Istinqoiyyah method in learning Arabic by not seeing any differences in the ability to master Arabic. The problem formulation in this study is